Weed Management Strategies in Soybean: Assessing the Influence of Integrated Nutrient and Weed Management on Weed Dynamics and Dry Weight - Rathod Sridhar; L. T. Longkumer; A. P. Singh; T. Gohain; G. Zion; N. Kikon; I. Ao (International Journal of Economic Plants, 2025)
A field investigation was conducted during the kharif seasons (July to October) of 2023 and 2024 at the Agronomy Farm, School of Agricultural Sciences, Nagaland University, Medziphema campus, Nagaland, India, to evaluate the effect of integrated nutrient and weed management on weed dynamics and weed dry matter in soybean (Glycine max L.). The experiment was laid out in a randomized block design (RBD) with three replications comprising four nutrient management treatments and four weed management practices. The pooled results revealed that 50% RDF+FYM @ 6 t ha-1+PSB @ 20 g kg-1 seed (N3) recorded reduced total weed density (79.0 plants m-2) and dry matter accumulation (6.70 g m-2) at 30 DAS. The sequential application of Pendimethalin @ 750 g ha-1 (PE) followed by Imazethapyr @ 75 g ha-1 (PoE) (W4) significantly lowered weed density and dry weight at all crop stages, with weed control efficiency (WCE) of 69.7%, 94.6%, and 95.6% at 15, 30, and 45 DAS, respectively. It was followed by Imazethapyr @ 75 g ha-1 (PE)+ one hand weeding at 25 DAS (W2), which also showed effective control and high WCE values (up to 93.8%). Nutrient treatments had non-significant effects on weed parameters but contributed indirectly to weed suppression via enhanced crop growth. Interaction effects (N×W) were statistically non-significant. The study confirms that sequential herbicide applications along with partial organic nutrient sources offer a sustainable approach to weed control and soil fertility improvement in rainfed soybean.